Prenatal treatment of severe fetal hemolytic disease due to anti-M alloimmunization by serial intrauterine transfusions - Lin Li; Linhuan Huang; Guangping Luo; Yanmin Luo; Qun Fang (Elsevier, 2017)
Objective: Fetal hemolytic disease is a common cause of fetal hydrops and fetal morbidity and mortality. Despite its relatively low frequency, the anti-M IgG antibody is one of the causes of severe fetal anemia and intrauterine death; only a few cases have been reported. Case report: This is a case of a pregnant woman with a history of three intrauterine deaths. A diagnosis of severe fetal anemia attributed to anti-M alloimmunization was confirmed in her fifth pregnancy. She came to our center for regular monitoring at the beginning of the pregnancy. Five intrauterine transfusions were performed to correct moderate to severe fetal anemia throughout her pregnancy. A male infant, delivered at the 36th gestational week received two transfusions after birth, and no neurologic abnormalities were observed until the child was 6 months of age. Conclusion: Anti-M alloimmunization is an important cause of severe fetal hemolytic disease. The characteristics of fetal hemolytic disease due to anti-M alloimmunization may be somewhat different from those of disease due to anti-D alloimmunization.